Preliminary Studies on the Fertility Status of the Soils of Sriganganagar District, Rajasthan - Kumar, Vinod; Mathur, G S; Seth, S P (Annals of Arid Zone, 2016)
Preliminary studies on the soil fertility status of Sri Ganganagar soils were made. For this purpose in all 447S surface soil samples have been analysed. The soils can be grouped into three soil groups i. e. Desert, Sierozems and Reverine. The nutrient index values for these soil groups show that Desert and Sierozems soils are poor in organic matter status. while Reverine soils are medium in this respect. Desert soils are also poor in available P and K and normal. in reaction, while Sierozems are medium in available P and K. Reverine soils are tending to become alkaline with low available P and medium available K content.